THE USE OF ART THERAPY METHODS IN THE WORK OF A PSYCHOLOGIST FOR THE CORRECTION OF ANXIOUS STATES OF PERSONALITY - Olena V. Karapetrova (Alfred Nobel University Publisher, 2020)
Unstable development of modern society with its socio-economic problems, uncertainty in the future, the growth of violence in society is increasingly the cause of emergence and development of anxious states of personality. Human life is accompanied by frequent experiences of negative modality, which leads to the manifestation of high anxiety disharmonizing social life, formation and development of personality. The article is devoted to the problem of occurrence and correction of anxious states of personality. It investigates the issue of using art therapy methods in the work of a psychologist for the correction of anxiety. It is determined that the purpose of art therapy, which is a specialized form of psychotherapy and based on art, is to harmonize the development of personality through the development of the ability to express oneself, to understand oneself. Scientific approaches to the development of art therapy in modern practical psychology for environmental psychotherapeutic care of the individual are analyzed. The essence of the concepts of "anxiety" and "worry" is presented, it is proved that there are similarities and differences between these concepts. Anxiety is defined as an emotional state that arises in a situation of uncertain danger and manifests itself in anticipation of unfavorable developments, and worry is an experience of emotional discomfort associated with the expectation of negative developments. Causes, preconditions and manifestations of anxiety states of personality are described. The analysis of the scientific literature of domestic psychologists and psychotherapists on the definition and presentation of techniques, programs of positive work with anxiety and worry of children and adults was made. The types of modern directions of art-therapeutic work of painting therapy, fairy-tale therapy, sand therapy were characterized. It is proved that the use of these types of art therapy in the work of a practical psychologist with anxiety, worry and anxiety states is effective. The examples were given of techniques for the use in therapeutic work with clients of different ages, personal development and psychological characteristics. It is concluded that nowadays the art therapy is both a technique of mental harmonization and human development, a means of resolving internal conflicts of personality and a means of activating the creative potential of an individual, the technique of activating resources and spreading the range of self-regulation. Using such types of art therapy as painting therapy, fairy-tale therapy, sand therapy when working with anxiety, fears, anxiety states, we can achieve high results in terms of professionalism of the psychologist and create a positive development situation for the client